2016
DOI: 10.1039/c6ra02143c
|View full text |Cite
|
Sign up to set email alerts
|

Isocyanide-based multicomponent reactions in the synthesis of heterocycles

Abstract: In this review, we try to update our previous presentation, underscoring the recent applications of isocyanides as privileged synthons in the synthesis of various heterocyclic compounds, especially, focused on those, synthesized via multicomponent reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(53 citation statements)
references
References 272 publications
(303 reference statements)
2
51
0
Order By: Relevance
“…Nitrogen adsorption–desorption isotherm of Ag@HNTs‐T is illustrated in Figure . As depicted, the shape of the isotherm of Ag@HNTs‐T is of type II nitrogen adsorption–desorption isotherm with H3 hysteresis loops, indicating the porous entity of the catalyst. To provide more insight into the textural properties of the catalyst and elucidate how functionalization of HNTs with 1 H ‐1,2,3‐triazole‐5‐methanol and immobilization of silver nanoparticles affect the textural features of pristine HNTs, total pore volume, average pore diameter and surface area of the catalyst were compared with those of pristine HNTs, Table .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Nitrogen adsorption–desorption isotherm of Ag@HNTs‐T is illustrated in Figure . As depicted, the shape of the isotherm of Ag@HNTs‐T is of type II nitrogen adsorption–desorption isotherm with H3 hysteresis loops, indicating the porous entity of the catalyst. To provide more insight into the textural properties of the catalyst and elucidate how functionalization of HNTs with 1 H ‐1,2,3‐triazole‐5‐methanol and immobilization of silver nanoparticles affect the textural features of pristine HNTs, total pore volume, average pore diameter and surface area of the catalyst were compared with those of pristine HNTs, Table .…”
Section: Resultsmentioning
confidence: 93%
“…Following our attempt for disclosing efficient and eco‐friendly protocols for the synthesis of chemicals through applying novel heterogeneous catalysts, we have recently focused our attention on the functionalization of HNTs with various functionalization agents and studying the utility of functionalized HNTs as efficient support for immobilization of catalytically active species such as heteropolyacid and ionic liquids . The results of our researches as well as other research groups clearly established that the functionality on the surface of HNTs has a significant role in efficient immobilization and suppressing the leaching of the catalytic species.…”
Section: Introductionmentioning
confidence: 86%
“…In the course of our research on heterogeneous catalysis, recently we reported the utility of CDNS and natural clays for immobilizing catalytic active species . In this line, it was found that the hybridization of inorganic supports with CDNS can lead to an improvement of the catalytic performance of the resulting catalyst .…”
Section: Introductionmentioning
confidence: 99%
“…MCRs have been also applied in polymer [74], nucleoside [75] and carbohydrate [76] chemistry. Main field of application remains the production of heterocyclic compounds and many natural products by means of MCR [38,[77][78][79][80][81][82][83][84][85][86][87][88][89], leading directly towards drug design and discovery [90][91][92][93][94]. Scheme 9 presents a current brief of well-known multicomponent reactions [35,40,9,[95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110].…”
Section: Methodsmentioning
confidence: 99%